Inguinal Exploration for the Management of Impalpable Undescended Testes - Thapa, Bijay; Pun, Madhusudan (Journal of Nepal Paediatric Society, 2017)
Introduction: The primary goal of surgical intervention with an impalpable testis is to locate and reposition the gonad. There has been much debate in the management of impalpable undescended testes. Many centres still advocate the role of open inguinal exploration in impalpable testes. Materials and methods: This retrospective study included 35 male patients. The clinical notes were reviewed for details of age at operation, side, location and condition of testes intraoperatively and the type of operation performed. Standard approach of inguinal explorations was performed under general anaesthesia. Follow up in first week and after 3 months was done. Results: 25(71.42%) impalpable testes were in left side, 9(25.71%) were on right side and 1(2.85%) was bilateral. At exploration 17(47.22%) were intracanalicular, nine (25%) were intraabdominal with seven low and two high,49(11.11%) were scrotal and six (16.66%) were absent, seven (41.17%) canalicular testes underwent orchidopexy and 10(58.22%) underwent gonadectomy for atrophied testes. Seven (77.77%) low abdominal testes were brought down to scrotum and two (22.22%) high abdominal were brought down to lower inguinal area as a first stage surgery. All 4(100%) scrotal testes were atrophied and gonadectomy performed. Six patients were diagnosed anorchia, 14 (87.5%) of impalpable testes that underwent orchidopexy were in a follow up with excellent results. One high first stage orchidopexy and another canalicular testes were found to have atrophied who did orchidectomy in follow-up. Conclusion: Inguinal exploration is a safe, reliable and successful surgical procedure for the management of impalpable testes including intraabdominal testes without procedure related complications.